Infectious mid basilar artery aneurysm from Pseudomonas meningitis. (16th June 2011) - Yu, Wengui; Rickert, Kim; Flores, Bruno; Samson, Duke
Abstract : Pseudomonas aeruginosa meningitis is an uncommon complication of neurosurgical procedures or head trauma. Here, a case of infectious mid basilar artery aneurysm from Pseudomonas meningitis, and its angiographic remission from timely antibiotic therapy, is reported.